2016
DOI: 10.15585/mmwr.mm6525a1
|View full text |Cite|
|
Sign up to set email alerts
|

Suicide Rates by Occupational Group — 17 States, 2012

Abstract: In 2012, approximately 40,000 suicides were reported in the United States, making suicide the 10th leading reported cause of death for persons aged ≥16 years (1). From 2000 to 2012, rates of suicide among persons in this age group increased 21.1%, from 13.3 per 100,000 to 16.1 (1). To inform suicide prevention efforts, CDC analyzed suicide by occupational group, by ascribing occupational codes to 12,312 suicides in 17 states in 2012 from the National Violent Death Reporting System (NVDRS) (2). The frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 4 publications
0
69
0
1
Order By: Relevance
“…Although farming, fishing, and forestry employees reported the lowest adjusted prevalences of every adverse HRQOL measure, another study that was not limited by self-reporting bias found that farming, fishing, and forestry employees had the highest rate of suicide among occupation groups. 33 Comparison of this study with that one suggests that farming, fishing, and forestry workers are reluctant to report poor HRQOL or that economic stress or workplace isolation may increase their suicide rates.…”
Section: Discussionmentioning
confidence: 74%
“…Although farming, fishing, and forestry employees reported the lowest adjusted prevalences of every adverse HRQOL measure, another study that was not limited by self-reporting bias found that farming, fishing, and forestry employees had the highest rate of suicide among occupation groups. 33 Comparison of this study with that one suggests that farming, fishing, and forestry workers are reluctant to report poor HRQOL or that economic stress or workplace isolation may increase their suicide rates.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies demonstrated the rate of suicide was highest among persons working in the farming, fishing, and forestry group (84.5/100,000), while the lowest rate was found in the education, training, and library occupational group (7.5/100,000) 64,65. While tick-borne disease exposure could be a contributor to those working in farming and forestry, it might not explain the high rate in fisherman 66.…”
Section: Introductionmentioning
confidence: 99%
“…1 Finally, a study of women firefighters found rates of career suicidal ideation and attempts to be 37.7% and 3.5%, respectively [5]. Converging research has highlighted that protective service workers, a category inclusive of firefighters, evince relatively higher rates of death by suicide [6,7], underscoring the need to understand factors that may amplify suicide risk among firefighters in order to inform prevention and intervention efforts.…”
Section: Introductionmentioning
confidence: 99%